Innovation platforms for solving marketing inefficiencies [Tanzania] - Ogenga, Frederick (Technical Centre for Agricultural and Rural Cooperation, 2018)
In Masalala, north-western Tanzania, the creation of an innovation platform has helped to improve smallholder paddy production and reduce inefficiencies in access to inputs and credit. Other value chains actors, including millers and buyers, have also benefitted from an improved supply of better quality paddy.